Beyond the humanitarian savior logics? UNHCR's public communication strategies for the Syrian and Central African crises. (March 2023) - Ongenaert, David; Joye, Stijn; Machin, David
Forcibly displaced people often face restrictive migration policies and stereotypical discourses. Therefore, this study analyzes UNHCR's public communication strategies towards the Syrian and Central African crises. Through a comparative-synchronic multimodal critical discourse analysis (MCDA) of UNHCR's (international) press releases (N = 28), news stories (N = 233), photos (N = 462) and videos (N = 50) of 2015, we examined its main representation and argumentation strategies. First, we found that UNHCR primarily represents forcibly displaced people in its press releases and news as victimized and/or voiceless masses, reproducing humanitarian savior and deservingness logics. However, stories, photos, and videos frequently portray them also as empowered individuals. This can be partially explained by media logics and political and private sector discourses and agenda-building opportunities. Moreover, UNHCR mainly voices pity-based and post-humanitarian Self-oriented solidarity discourses, and links protection to states' (perceived) interests. Finally, these discursive strategies respond to dominant migration management paradigms and the increasingly neoliberalized, political realist international refugee regime (IRR).